Information and support to patients when the waiting time guarantee cannot be fulfilled: a qualitative study - Belén Casales Morici; Hanna Augustsson; Henna Hasson; David Ebbevi (BMC, 2023)
Abstract Background Long waiting times for health care services are a prominent health policy issue. Waiting time guarantees may limit time to assessment and treatment. Methods This study aims to investigate the information and support given to patients when the waiting time guarantee cannot be fulfilled from a care provider and administrative management perspective. Semi-structured interviews (N = 28) were conducted with administrative management and care providers (clinic staff and clinic line managers) in specialized clinics in the Stockholm Region, Sweden. Clinics were purposefully sampled for maximum variation in ownership (private, public), complexity of care, geographical location, volume of production, and waiting times. Thematic analysis was applied. Results Care providers reported that patients received inconsistent information and support with regard to the waiting time guarantee and that information was not adapted to health literacy or individual patient needs. Contrary to local law, they made some patients responsible for finding a new care provider or arranging a new referral. Furthermore, financial interests affected whether patients were referred to other providers. Administrative management steered care providers' informing practices at specific time points (upon establishment of a new unit and after six months of operation). A specific regional support function, Region Stockholm's Care Guarantee Office, helped patients change care providers when long waiting times occurred. However, administrative management perceived that there was no established routine to assist care providers in informing patients. Conclusions Care providers did not consider patients' health literacy when informing them about the waiting time guarantee. Administrative management's attempts to provide information and support to care providers are not producing the results they expect. Soft-law regulations and care contracts seem insufficient, and economic mechanisms undermine care providers' willingness to inform patients. The described actions are unable to mitigate the inequality in health care that arises from differences in care-seeking behavior.